Professional services : - Delong, Thomas (McGraw-Hill/Irvin, 2003)
DeLong and Nanda's Professional Services: Text and Cases is the first casebook to be published on the management of professional service firms (law firms, architecture, financial services, consulting). It includes a comprehensive selection of case studies that span these industries broadly. Although much has been researched and written about managing service firms generally (e.g., food service, hotels, banking and other consumer services), very little has been compiled on managing professional services. Professional Service firms have a highly educated employee base and these firms offer both consumer and commercial services that involve managing, supporting and improving their clients' intellectual assets. Delong and Nanda have developed this text to demonstrate to students the unique challenges and opportunities attendant upon this market segment of our economy.